ELISA determination of IgG antibodies to pneumococcal capsular polysaccharides in a group of children. - Windebank, K; Faux, J; Chapel, H (1987)
An enzyme-linked immunosorbent assay (ELISA) was developed to measure specific IgG antibody levels to pneumococcal polysaccharide antigens in 300 children attending various hospital departments. By expressing the results as a specific binding index (SBI) of given high and low controls, good reproducibility was obtained. Serum levels of the antibodies were found to fall rapidly during the 1st year of life, plateau during the 2nd and then rise steadily, reaching adult levels by the 7th year.